Primary lymphoma of the breast: A case report and review of the literature - Yoneyama, Kimiyasu (Radiol Case Rep, 2020)
Primary lymphoma of the breast is a rare disease, accounting for about 0.5% of all primary breast tumors. Often found as a solitary indolent mass, it is difficult to distinguish from breast cancer on imaging and is often diagnosed for the first time based on histological findings. Diffuse large B-cell lymphoma is the most common histological subtype. A 48-year-old woman visited our hospital because of a painless mass in the left breast. Breast cancer was suspected based on the imaging findings. A core needle biopsy was performed, and the invasive ductal carcinoma was diagnosed. Partial mastectomy and sentinel lymph node biopsy were performed. The resected specimen was finally diagnosed as diffuse large B-cell lymphoma based on immunohistochemical staining. The patient was treated with R-CHOP and intrathecal injection of methotrexate. The patient remains alive without recurrence 4 years later. Awareness of primary breast lymphoma is essential for accurate and timely diagnosis and avoidance of unnecessary surgery.